Analisis Kinerja Guru Tidak Tetap dalam Meningkatkan Akademik Peserta Didik SMA Dharma Wanita 1 Gedangan - Yusti Oktavian, Riske; Naili Rahma, Syeima; Trihantoyo, Syunu (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
In an institution, especially a school, there must always be a program to improve the quality in it. Supporting factors for the running of a quality improvement program require educators who are able to run the program well. Teachers take an important role in the world of education in charge of educating and guiding students. The performance of teaching staff must pay great attention to the implementation of, and in a private school there are permanent teacher educators and non-permanent teachers. The distinction between the two is that non-permanent teachers are needed when there is a shortage of educators and another distinction is that they do not have positions, so they only assist permanent teachers, even so this can provide opportunities for college graduates who want to become teachers to have the opportunity to develop competencies and careers. This research is intended to find out the performance of non-permanent teachers in improving the academic quality of Dharma Wanita 1 Gedangan High school Students